Diabetic foot ulcer early detection - Awad, Muath; Abo Homyd, Mohammad; Karajeh, Ahmad (جامعة بوليتكنك فلسطين - اجهزة طبية, 2019)
مرض السكري من الامراض المزمنة التي تواجه الانسان ومع مرور الزمن ربما يصاحبه مضاعفات ناتجة عن المرض، وهو مرض قرحة القدم السكرية وهو مرض خطير قد يؤدي الى بتر القدم في حال لم يعالج في بداياته، وهذا المرض ينتج بسبب ضعف سريان الدم او اعتلال في الاعصاب الطرفية وهؤلاء المرضى يحتاجون الى عناية خاصة بأقدامهم. لذا قمنا بجمع المعلومات والأفكار حول مرض قرحة القدم السكرية لإفادة هؤلاء المرضى، فكانت الفكرة الأساسية أن نقوم بتصميم أداة تقوم على الكشف المبكر لمرض قرحة القدم السكرية وذلك من خلال طريقتين: الاولى الإشارة الكهربائية لعضلة القدم حيث ان مرض السكري او القدم السكرية يؤثر بشكل واضح على هذه الإشارة الناتجة من حيث الشكل أو قيمة الجهد الناتج.وقد تم استنتاج أن الإشارة الكهربائية للعضلة تتأثر مع التقدم بالعمر وتتأثر بازدياد الوزن ومدة الإصابة بمرض السكري، وأن قيمة الجهد الناتجة تتأثر فكانت في حالة قرحة القدم السكرية بالنسبة للأشخاص السليمين تتراوح ما بين (19.2-0.99), وفي حالة المصابين بمرض السكري بالنسبة للأشخاص السليمين تتراوح ما بين ((64.1-30.7. أما الثانية وهي عن طريق وضع مجسات في اماكن محددة داخل ضبانة ويقوم المريض بالضغط على هذه الضبانة عن طريق الوقوف عليها فقط فتقوم المجسات باستشعار الضغط الناتج من القدم على الضبانة ومن خلال قيمة الضغط الناتجة يتم معرفة إذا كان المريض مصاب بمرض القدم السكرية ام لا. وقد تم استنتاج أن الضغوط في المناطق الأربعة يمكن ترتيبها على النحو التالي: أن الضغط في منطقة الكعب يكون أعلى من باقي المناطق ومن ثم منطقة الأصبع الكبير ومن ثم منطقة الوسادة ومن ثم منطقة القدم الجانبية. وأن المناطق الأكثر عرضة للإصابة بمرض قرحة القدم السكرية هي منطقة الأصبع الكبير ومنطقة الوسادة. Diabetes is one of the chronic diseases that a person faces with the passage of time, it may be accompany by complications resulting from the disease, which is a diabetic foot ulcer disease and it is a serious disease that may lead to amputation of the foot if it was not treated at its beginning. In addition, these patients need special care for their feet. Therefore, we collected information and ideas about diabetic ulcer disease to benefit these patients. Therefore, the basic idea was to design a tool based on early detection of diabetic foot ulcer disease through two methods: The first is the electrical signal of the foot muscle where diabetes or diabetic foot ulcer affects. This resulting signal is in terms of the shape or value of the output voltage. After that, it was concluded that the electrical signal of the muscle is affected with age and is affected by the increase in weight and the duration of diabetes, and that the value of the resulting effort is affected and was in the case of diabetic foot ulcers. In the case of foot ulcers in the ratio between (19.2-0.99), and in the case of diabetes for healthy people, it occurs ratio between (64.1-30.7).The shape of the signal changes and appears differently apparently when displayed, whether it is the signal of a diabetic foot ulcer patient, a diabetic patient, or a healthy person. The second is by placing sensors in specific places inside the insole and the patient presses this insole by standing on it only. The sensors sense the pressure from the foot on the insole and through the resulting pressure value it is known if the patient has diabetic foot ulcer or not. It has been concluded that the pressure in the four areas can be arranged as follows: that the pressure in the heel area is higher than the rest of the areas and then the big toe area and then the pad area and then the side foot area. The area’s most prone to developing diabetic ulcer disease are the big toe and the pad area.
CD , no of pages 83 , اجهزة طبية 3/2019
Keywords: early detection